Indigenous Peoples are critical to the success of nature-based solutions to climate change - Justine Townsend; Faisal Moola; Mary-Kate Craig (Canadian Science Publishing, 2020)
Nature-based solutions (NbS) to climate change mitigation-such as ecosystem protection or conservation, improved forest management practices, as well as afforestation-can significantly reduce global net emissions (Griscom et al. 2017; Seddon 2019). This is particularly the case when NbS are paired with emissions reductions and clean energy solutions (Anderson et al. 2019; Griscom et al. 2019; IPCC 2019). NbS could provide 30%-40% of the CO2 mitigation required by 2030 to help ensure warming is capped at under 2 °C (Seddon 2019). While holding great potential for effective climate change policy, some NbS measures such as protected areas and forest plantations can negatively impact Indigenous Peoples globally through displacement, livelihood restrictions, and ensuing cultural impacts (e.g., Osborne 2015; Vanclay 2017) and thus must be designed and implemented with Indigenous participation and consent if they are to be successful. These impacts intensify the disadvantages already faced by Indigenous communities, including human rights violations, discrimination, and poverty (Chatty and Colchester 2002; Dowie 2009; United Nations 2009). Indigenous Peoples are also more vulnerable to the impacts of climate change including food insecurity; displacement as a result of catastrophic flooding, drought, and fires; and threats to critical infrastructure (Havemann 2009; Ford 2012; Williams 2012; Lynn et al. 2013).